Implementing psychological therapies for functional GI disorders in children and adults. (1st September 2016) - Reed-Knight, Bonney; Claar, Robyn Lewis; Schurman, Jennifer Verrill; van Tilburg, Miranda A.L.
ABSTRACT: Introduction: Functional GI disorders (FGIDs) are common in adults and children. Psychological factors play an important role in the onset and maintenance of FGIDs and in explaining the associated disability. Psychological treatments such as Cognitive Behavioral Therapy and Hypnotherapy have been found efficacious in FGIDs but Integrating psychological treatments into traditionally medically-oriented care can be challenging. Areas covered: This review outlines the case for integrating psychological therapies into medical care for FGIDs and examine various models of integrated care that can be adapted to fit specific practice scenarios. Expert commentary: We advise integrating a psychologist in the care and treatment planning of every patient. Clinic-specific needs dictate how integrated care for patients with FGIDs can be delivered.